Growing up under Mao and Deng: On the ideological determinants of corporate policies - Hao Liang; Rong Wang; Haikun Zhu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
Economic activities have always been organized around certain ideologies, yet little is known about how ideology shapes corporate behavior and how it is different from other political forces. We investigate the impact of politicians' ideology on corporate policies by exploring a unique setting of ideological change in China from Mao's ideology to Deng's around 1978. Using textual analysis based on keywords in People's Daily, we find a discontinuity in ideological exposure among people who later became city mayors. Those who were at least 18 years old in 1978 and had joined the Chinese Communist Party (CCP) are more likely to have adopted Mao's ideology, and those who did not join by 1978, due to age limit, but joined soon thereafter were more likely to have adopted Deng's ideology. This ideological difference has had an enduring effect on contemporary firm and city policies. Firms in cities governed by mayors with Mao's ideology have made more social contributions, lowered within-firm pay inequality, and pursued less internationalization than those with Deng's. These effects are stronger in firms with political connections, less state ownership, and more government subsidies as well as in regions that are more market-oriented and not "revolutionary bases." Our results are robust to OLS regressions with various pair fixed effects besides regression discontinuity. We further find that corporate policies promoted by Mao's ideology are associated with slower firm growth but greater stakeholder engagement.
URN:NBN:fi:bof-202008272299
Keywords: G30; M14; P16; 330; political ideology; corporate policy; regression discontinuity; China